Relefansi Sharing Economy dalam Pengembangan UMKM Pasca Covid-19 - Anfas Anfas (IPM2KPE, 2022)
The purpose of this study was to determine the relevance of the sharing economy in the development of SMEs after COVID-19. This research method is library research. This research is studied using the concept of switching behavior approach by Boyle. The results show that, from the push aspect, the increasingly modern development of IT and the ability to reach market share are the reasons for sharing economy companies to survive and grow. From the pull aspect, the high level of profit and the lack of regulations governing the sharing economy have made many large companies invest in companies based on the sharing economy. Lastly, from the mooring aspect, the number of internet users and the instant behavior of millennials, make the sharing economy a business sector that still exists because it already has a mooring in the form of a large market share and the number is very large. The conclusion is that the sharing economy will still be relevant in developing MSMEs after the COVID-19 pandemic. Keywords: Mooring, Pull, Push, Sharing Economy, Switching Behavior, UMKM